2011
DOI: 10.1039/c1nr10594a
|View full text |Cite
|
Sign up to set email alerts
|

Electronic and magnetic properties of pristine and chemically functionalized germanene nanoribbons

Abstract: We perform a spin polarized density-functional theory (DFT) study of the electronic and magnetic properties of pristine and chemically doped germanene nanoribbons (GeNRs) with different widths. It is found that the Ge atom at the ribbon edge always prefers to be substituted by an impurity atom. Our study reveals that a single N or B atom substitution induces a semiconducting-metal transition in armchair oriented germanene nanoribbons (AGeNRs) as evidenced by the appearance of a half-filled band with less dispe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
66
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(73 citation statements)
references
References 58 publications
7
66
0
Order By: Relevance
“…8 Germanene has the same honeycomb structure as graphene, but the atoms are buckled, resulting in increased stability and improved carrier transport characteristics in comparison to graphene. Moreover, the electronic structure of germanene is quite similar to graphene.…”
Section: -5mentioning
confidence: 99%
“…8 Germanene has the same honeycomb structure as graphene, but the atoms are buckled, resulting in increased stability and improved carrier transport characteristics in comparison to graphene. Moreover, the electronic structure of germanene is quite similar to graphene.…”
Section: -5mentioning
confidence: 99%
“…The electronic properties of the edge states of silicene, germanene and stanene nanoribbons (SiNRs, GeNRs, SnNRs) with and without hydrogen termination have also been studied using a single-orbital tight-binding model [4,7] and first-principles calculations [37][38][39][40][41] by many groups. Although the single-orbital model can reproduce the bulk energy dispersion [42], it has not yet been clarified whether the single-orbital model can really express the various types of edge states with hydrogen termination [4].…”
Section: Introductionmentioning
confidence: 99%
“…Pang et al investigated the electronic and magnetic properties of both pristine and chemically doped GeNRs and found that a single B or N substitution can induce a transition from semiconducting to metal in armchair GeNRs. 116 In addition, a single B or N doping turns AFM-semiconducting zigzag GeNRs into FM-semiconductor. Bayani et al studied the optical properties of hydrogenated GeNRs and the properties of H sensitive FET based on GeNRs.…”
Section: B Nrs Of Germanene and Stanenementioning
confidence: 99%